Radiotherapy for Rectal Cancer and Radiation-Induced Malignancies from Epidemiological and Dosimetric Data - Stefanos Kachris; Michalis Mazonakis (Applied Sciences)
Preoperative or postoperative radiation therapy is broadly employed in patients with rectal carcinoma. Radiotherapy directs high-energy beams of ionizing radiation toward the tumor area to destroy cancer cells. High radiation doses are needed for cell killing. The radiation exposure of the healthy tissues/organs may lead to carcinogenesis. This study describes the evolving role of radiotherapy in rectal cancer management. The present report also reviews epidemiological and dosimetric studies related to the radiation-induced second malignancies from pelvic radiotherapy. Some epidemiological studies have concluded that the second-cancer risk in patients subjected to radiation therapy does not increase compared to unexposed rectal cancer patients. Other researchers found an elevated or a marginally increased probability for second-cancer induction. Dosimetric studies reported cancer risk estimates for critical organs or tissues in the near and far periphery of the treatment volume. Useful information about the effect of the treatment parameters such as the irradiation technique, photon beam energy, and fractionation schedule on the organ-specific second-cancer risk was derived from the dose data analysis. The knowledge of these effects is needed for the selection of the optimal treatment parameters enabling a reduction in the resultant risk of carcinogenesis.